(untitled) (Alberta Journal of Educational Research, 2007)
Despite the constitutional ban on the practice of untouchability and caste-based discrimination, this article elaborates on a gendered-caste-based discriminatory reality in rural India, the difficulties of enforcing legal remedies, and on related human rights praxis to address gendered-caste atrocities by drawing on the experiences of a Canadian voluntary development nongovernmental organization (NGO) that has been working with Dalits (downtrodden/scheduled caste groups) in India for over a decade. This experience suggests that although there is a significant role for human rights education in addressing gendered-caste atrocities, there are cultural and political limits to a rights-based approach that privilege the individual and a politics of vocal, open democratic resistance.